Manajemen Dakwah Pondok Pesantren (Pendidikan Tradisional) - Shofiyullahul Kahfi; Emi Fahrudi (Program Studi Manajemen Dakwah, Fakultas Dakwah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Pesantren as representatives of institutions that foster the community, are expected to prepare a number of community development plans, as well as to improve the internal quality of Islamic boarding schools as well as to improve the external quality of the community. In order to carry out his da'wah to apply the teachings of amar ma'ruf and nahi munkar. Da'wah cadres or santri need to get coaching, guidance and counseling through traditional Islamic boarding schools which are fostered by a kyai and their ustadz, especially those relating to cognitive, psychomotor behaviors in terms of the process of teaching and learning activities such as the implementation of teaching practices, Bahtsul Masail activities, book deliberations, khitobah, sending students to the prayer room or mosque around The path of da'wah is very broad, long and unpredictable the difficulties in it. Therefore, the students or candidates who are recruited for da'wah who will pass this way should do a lot of things to get professionally prepared. Because the challenges in preaching are very broad, good da'wah management is needed. Da'wah management is a series of processes that run continuously in regulating or regulating da'wah activities so that they run according to plan and on target. The optimal achievement of da'wah goals can only be realized by organizing da'wah activities.